Vibrational Analysis of Conducting Nanocomposite Actuator - Gariya, Narendra; Prasad, Brijesh; Kumar, Pushpendra; Panwar, Varij (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*304.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.988741);" role="presentation">The focus of this study is on <span dir="ltr" style="left: calc(var(–scale-factor)*198.29px); top: calc(var(–scale-factor)*304.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.956565);" role="presentation">flexible actuators which act as soft muscles and can produce large amount of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*317.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.916776);" role="presentation">deflection (bending) on the application low voltage less than 4V, which can be applied for various applications of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91018);" role="presentation">robotic arms, manipulators, medical devices, aerospace applicati<span dir="ltr" style="left: calc(var(–scale-factor)*331.87px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93378);" role="presentation">ons and for structural health monitoring. In this <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.943949);" role="presentation">study, vibration analysis of beam structure of polymer composite of (PVDF/CNF) material is carried out using <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918072);" role="presentation">Finite element analysis. The vibration analysis is carried out for six modes with <span dir="ltr" style="left: calc(var(–scale-factor)*391.99px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.898783);" role="presentation">one end fixed a<span dir="ltr" style="left: calc(var(–scale-factor)*453.34px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907307);" role="presentation">nd both <span dir="ltr" style="left: calc(var(–scale-factor)*485.98px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920616);" role="presentation">end fixed <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912576);" role="presentation">boundary conditions. <span dir="ltr" style="left: calc(var(–scale-factor)*158.18px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907776);" role="presentation">The <span dir="ltr" style="left: calc(var(–scale-factor)*175.94px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.89567);" role="presentation">obtained <span dir="ltr" style="left: calc(var(–scale-factor)*212.45px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.88771);" role="presentation">results <span dir="ltr" style="left: calc(var(–scale-factor)*240.65px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918277);" role="presentation">from the analysis showed the minimum failure frequency with different <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901306);" role="presentation">mode shapes at di<span dir="ltr" style="left: calc(var(–scale-factor)*145.46px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931558);" role="presentation">fferent boundary conditions. The analysis <span dir="ltr" style="left: calc(var(–scale-factor)*317.95px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.885111);" role="presentation">can be <span dir="ltr" style="left: calc(var(–scale-factor)*347.71px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.953744);" role="presentation">very much helpful in prediction of the safe <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*396.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.957928);" role="presentation">working conditio<span dir="ltr" style="left: calc(var(–scale-factor)*140.54px); top: calc(var(–scale-factor)*396.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906141);" role="presentation">ns for the complex structures.